2014
DOI: 10.1136/bmjopen-2013-003431
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy study of natural health product adverse reactions (SONAR): a cross-sectional study using active surveillance in community pharmacies to detect adverse events associated with natural health products and assess causality

Abstract: ObjectivesTo investigate the rates and causality of adverse event(s) (AE) associated with natural health product (NHP) use, prescription drug use and concurrent NHP-drug use through active surveillance in community pharmacies.DesignCross-sectional study of screened patients.Setting10 community pharmacies across Alberta and British Columbia, Canada from 14 January to 30 July 2011.ParticipantsThe participating pharmacy staff screened consecutive patients, or agents of patients, who were dropping or picking up pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
0
23
1
Order By: Relevance
“…6 Despite the fact that natural health products may be perceived as safe because of their natural origins, researchers have demonstrated the potential for serious toxicity and possible adverse reactions or events, especially in patients taking prescription medications concurrently. 85 Compounding this risk is the fact that safety standards that specifically address the pediatric population are lacking, 86 and parents may be reluctant to disclose the use of natural products for fear of censure or ridicule. 6 Failure of pharmacists and physicians to routinely inquire about natural health product use is another significant compounder.…”
Section: Biologically Based Practicesmentioning
confidence: 99%
“…6 Despite the fact that natural health products may be perceived as safe because of their natural origins, researchers have demonstrated the potential for serious toxicity and possible adverse reactions or events, especially in patients taking prescription medications concurrently. 85 Compounding this risk is the fact that safety standards that specifically address the pediatric population are lacking, 86 and parents may be reluctant to disclose the use of natural products for fear of censure or ridicule. 6 Failure of pharmacists and physicians to routinely inquire about natural health product use is another significant compounder.…”
Section: Biologically Based Practicesmentioning
confidence: 99%
“…At the same time, it is clear that some herbal supplements could put patients at risk for harm when those patients use these kinds of supplements concomitantly with prescription drugs . In a study of 10 community pharmacies in which the use of natural products and adverse reactions were explored, it was found that patients who used natural supplements together with their prescribed medications had a 6.4 times higher risk of experiencing adverse reactions than did those patients taking only their prescribed medication (OR; 95 CI, P < 0.001) . Furthermore, a systematic review from Alsanad et al .…”
Section: Introductionmentioning
confidence: 99%
“…[26,28,31] In a study of 10 community pharmacies in which the use of natural products and adverse reactions were explored, it was found that patients who used natural supplements together with their prescribed medications had a 6.4 times higher risk of experiencing adverse reactions than did those patients taking only their prescribed medication (OR; 95 CI, P < 0.001). [32] Furthermore, a systematic review from Alsanad et al [21] identified 167 theoretical interactions among the 433 participating patients with cancer taking supplements. Risk is aggravated by the fact that the decision about whether to use herbals is not always based on evidenced indications; in addition, patients tend to use various herbals simultaneously, which adds yet another element of risk.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed methods have been presented previously (9,10) In brief, adverse events were identified in a community pharmacy where participating pharmacists and pharmacy staff were systematically asking patients collecting prescriptions for conventional medicines whether they had recently been taking NHPs such as herbal medicines, vitamins, minerals or other supplements together with prescription medications and whether they had experienced an unwanted or unexpected effect. Where adverse events were identified, the study team then obtained informed written consent from the patient prior to an in-depth guided telephone interview.…”
Section: Active Surveillancementioning
confidence: 99%
“…A formidable challenge for pharmacovigilance of NHPs is the under-reporting of suspected adverse drug reactions associated with these products (7,8). The Pharmacy Study Of Natural health product Adverse Reactions (SONAR) is a multi-centre study assessing the feasibility of a community pharmacy-based active surveillance system to identify adverse reactions related to NHPs (9,10). The study identified a patient who presented with severe sedation after intake of melatonin with two antidepressants (citalopram and nortriptyline) and one opioid analgesic (oxycodone).…”
Section: Introductionmentioning
confidence: 99%